Retracing the Historicity of the Qur'an in Mainstream Islam and Critical Islam - A'azliansyah Farizil Anam; Taufiki Ali Ilhami; Muhammad Hafidza Daffa Nurdiansyah (Yayasan Pesantren Mahasiswa An-Nur, 2025)
This study arises from the urgency to reexamine the authenticity of the Qur'an in a historical context, amid debates among mainstream Islam, critical Islam, and Orientalist scholarship. The long history of the codification of the Qur'an, which involved the processes of revelation, memorization, and text standardization, became the basis for the emergence of two primary schools of thought: mainstream Islam, which affirms the purity of revelation through mutawatir transmission and divine protection, and critical Islam, which highlights the historical, social, and rational dimensions of the codification process without denying the sacredness of the text. Using a qualitative research method grounded in a literature review and historical and comparative analysis, this study finds that the debate over the authenticity of the Qur'an is not merely a conflict between faith and rationality, but rather a productive dialectic among faith, history, and scientific methodology. The results of the study show that both mainstream Islam and critical Islam, despite their differences in epistemological approaches, are essentially striving to maintain the integrity of revelation; one through strengthening theological aspects, and the other through rational and scientific historical verification.